2019
DOI: 10.5435/jaaos-d-18-00322
|View full text |Cite
|
Sign up to set email alerts
|

Autogenous Iliac Crest Bone Grafting for the Treatment of Fracture Nonunion Is Equally Effective in Elderly and Nonelderly Patients

Abstract: Introduction: Autogenous iliac crest bone graft (ICBG) is considered the benchmark graft for nonunion repair. However, ICBG harvest is invasive and may provide reduced benefit to elderly patients. The purpose of this study was to compare the clinical and functional outcomes of ICBG use in fixation of fracture nonunions between elderly and nonelderly patients. Methods: Over a 13-year period, 242 patients who underwent operative repair of a long bone fracture nonunion and received autogenous ICBG were enrolled i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Finally, the new-onset postoperative infection rate was significantly lower in the autograft group (12.4%), compared to the allograft cohort (26.3%) [21] . Autograft appears to be equally efficacious in the elderly patient as in the young [22] .…”
Section: Results Of Autologous Bone Graftingmentioning
confidence: 97%
“…Finally, the new-onset postoperative infection rate was significantly lower in the autograft group (12.4%), compared to the allograft cohort (26.3%) [21] . Autograft appears to be equally efficacious in the elderly patient as in the young [22] .…”
Section: Results Of Autologous Bone Graftingmentioning
confidence: 97%
“…Carlock et al found that the clinical outcomes of autogenous iliac crest bone graft (ICBG) for nonunion repair appeared to be as effective in elderly patients as in the young with a long bone nonunion, and ICBG is considered as the benchmark graft for nonunion repair among all age groups 52 , 53 . We speculate that high biocompatibility and osteoconduction of ICBG might bring a minimum burden for surrounding senescent cells/tissues compared with allotransplantation and artificial graft so that the accumulated senescent cell burden would not excess the threshold for self-regenation according to the above threshold theory.…”
Section: Discussionmentioning
confidence: 99%
“…Dawson et al reported a higher union rate in the ICBG cohort compared to the RIA group [ 24 ]. Carlock et al reported a high union rate after ICBG, with 232 unions in 242 treated patients [ 35 ]. Furthermore, On Salawu et al reported a higher union rate following ICBG, with 81 unions in 86 patients [ 36 ].…”
Section: Discussionmentioning
confidence: 99%